Discovery of Affinity‐Based Probes for Btk Occupancy Assays. (9th January 2019) - Qiu, Hui; Caldwell, Richard; Liu‐Bujalski, Lesley; Goutopoulos, Andreas; Jones, Reinaldo; Potnick, Justin; Sherer, Brian; Bender, Andrew; Grenningloh, Roland; Xu, Daigen; Gardberg, Anna; Mochalkin, Igor; et al.
Abstract: Bruton's tyrosine kinase (Btk) is an attractive target for the treatment of a wide array of B‐cell malignancies and autoimmune diseases. Small‐molecule covalent irreversible Btk inhibitors targeting Cys481 have been developed for the treatment of such diseases. In clinical trials, probe molecules are required in occupancy studies to measure the level of engagement of the protein by these covalent irreversible inhibitors. The result of this pharmacodynamic (PD) activity provides guidance for appropriate dosage selection to optimize inhibition of the drug target and correlation of target inhibition with disease treatment efficacy. This information is crucial for successful evaluation of drug candidates in clinical trials. Based on the pyridine carboxamide scaffold of a novel solvent‐accessible pocket (SAP) series of covalent irreversible Btk inhibitors, we successfully developed a potent and selective affinity‐based biotinylated probe12 (2‐[(4‐4‐[5‐(1‐5‐[(3a S, 4 S, 6a R )‐2‐oxo‐hexahydro‐1 H ‐thieno[3, 4‐ d ]imidazol‐4‐yl]pentanamido‐3, 6, 9, 12‐tetraoxapentadecan‐15‐amido)pentanoyl]piperazine‐1‐carbonylphenyl)amino]‐6‐[1‐(prop‐2‐enoyl)piperidin‐4‐yl]pyridine‐3‐carboxamide). Compound12 has been used in Btk occupancy assays for preclinical studies to determine the therapeutic efficacy of Btk inhibition in two mouse lupus models driven by TLR7 activation and type I interferon. Abstract : Recognize, react, report : We successfully developed affinity‐based probes for Bruton's tyrosine kinase (Btk) occupancy assays by using the scaffold of irreversible covalent Btk inhibitors in a pyridine‐carboxamide solvent‐accessible pocket (SAP) series. With installation of the linker and biotin moiety in the SAP area, the top probe molecule thus prepared showed single‐digit nanomolar potency and good kinome selectivity.